Quality of patient- and proxy-reported outcomes for children with impairment of the upper extremity: a systematic review using the COSMIN methodology - J. P. Ruben Kalle; Tim F. F. Saris; Inger N. Sierevelt; Denise Eygendaal; Christiaan J. A. van Bergen (SpringerOpen, 2022)
Abstract Background As patient-reported outcome measures (PROMs) have become of significant importance in patient evaluation, adequately selecting the appropriate instrument is an integral part of pediatric orthopedic research and clinical practice. This systematic review provides a comprehensive overview of PROMs targeted at children with impairment of the upper limb, and critically appraises and summarizes the quality of their measurement properties by applying the COnsensus-based Standards for selection of health Measurement INstruments (COSMIN) methodology. Methods A systematic search of the MEDLINE and EMBASE databases was performed to identify relevant publications reporting on the development and/or validation of PROMs used for evaluating children with impairment of the upper extremity. Data extraction and quality assessment (including a risk of bias evaluation) of the included studies was undertaken by two reviewers independently and in accordance with COSMIN guidelines. Results Out of 6423 screened publications, 32 original articles were eligible for inclusion in this review, reporting evidence on the measurement properties of 22 self- and/or proxy-reported questionnaires (including seven cultural adaptations) for various pediatric orthopedic conditions, including cerebral palsy (CP) and obstetric brachial plexus palsy (OBPP). The measurement property most frequently evaluated was construct validity. No studies evaluating content validity and only four PROM development studies were included. The methodological quality of these development studies was either 'doubtful' or 'inadequate'. The quantity and quality of the evidence on the other measurement properties of the included questionnaires varied substantially with insufficient sample sizes and/or poor methodological quality resulting in significant downgrading of evidence quality. Conclusion This review provides a comprehensive overview of currently available PROMs for evaluation of the pediatric upper limb. Based on our findings, none of the PROMs demonstrated sufficient evidence on their measurement properties to justify recommending the use of these instruments. These findings provide room for validation studies on existing pediatric orthopedic upper limb PROMs (especially on content validity), and/or the development of new instruments.